Evaluation of antimicrobial effect of azadirachtin plant extract (Soluneem ™) on commonly found root canal pathogenic microorganisms (viz. Enterococcus faecalis) in primary teeth: A microbiological study - Shanal Shah; Karthik Venkataraghavan; Prashant Choudhary; Shameer Mohammad; Krishna Trivedi; Shalin G Shah (Wolters Kluwer Medknow Publications, 2016)
Aim: The aim of this study is to evaluate the antimicrobial activity of Soluneem ™ when used as an irrigating solution along with other commonly used irrigating solution sodium hypochlorite (NaOCl) against Enterococcus faecalis. Materials and Methods: Microorganism used in this study was E. faecalis (Microbial Type Culture Collection 439). Test substance used was Soluneem ™, which was obtained from Vittal Mallya Scientific Research Foundation (VMSRF), Bengaluru. This study was conducted in a microbiology laboratory (Biocare Research India Pvt., Ltd. Laboratory, Ahmedabad, Gujarat) to evaluate the antimicrobial effect of Soluneem ™ (Azadirachtin) on E. faecalis. Antimicrobial activity testing was performed using the macrobroth dilution method according to the Clinical Laboratory Standards Institute guidelines. All determinations were performed thrice. Results: Minimum bactericidal concentration (MBC) was seen as 2.6% for Soluneem ™ while the same was seen at 0.1% for NaOCl. Independent sample t-test was carried out to compare the MBC of Soluneem ™ and NaOCl, which showed that there was no statistically significant difference between them, i.e., 2.6% Soluneem ™ was as effective as 0.1% NaOCl. Conclusion: Soluneem ™ showed antimicrobial activity against E. faecalis at various concentrations. It was also found that the efficacy of Soluneem ™ at 2.6% concentration and above was relatively similar to that of gold standard irrigating solution (NaOCl) on inhibition of E. faecalis.